2012
DOI: 10.1111/j.1470-6431.2012.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient care, satisfaction and service quality in health care

Abstract: It is becoming increasingly important in the healthcare setting to treat patients as consumers and measure their satisfaction with medical services rendered. As such, patient satisfaction should be considered an important output of a country's healthcare system, basically reflecting the stage of its development. The conducted study tested students’ satisfaction with the quality of service provided by student polyclinics. In particular, the study has analysed the impacts of personal relationships, promptness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 42 publications
5
69
1
14
Order By: Relevance
“…Senić and Marinković, 2012). Care assistants are nowadays expected to decode the needs of the older person and adapt their support thereafter.…”
Section: Quality Of Care and User-orientationmentioning
confidence: 99%
“…Senić and Marinković, 2012). Care assistants are nowadays expected to decode the needs of the older person and adapt their support thereafter.…”
Section: Quality Of Care and User-orientationmentioning
confidence: 99%
“…This has ultimately culminated in the present practice mandates of satisfactorily fulfilling the individual's healthcare needs and ensuring quality care [6,12]. PS measures have been instrumental in evaluating this objective, and in the current healthcare landscape are being used for two general purposes: 1) Marketing, and 2) Quality Assessment [2,13,14]. From a marketing perspective, maximizing PS can influence patient choice of care provider [15], resulting in significant financial benefits, such as increased profits, capitalizing on government incentives for meeting certain performance standards [e.g., 5,16,17] and service efficiency [6,18].…”
Section: Introductionmentioning
confidence: 99%
“…One study measuring student perceptions of service quality at a student health center (Canel & Anderson Fletcher, 2001) found there was a large gap between higher student expectations versus the perceptions of health center employees' "willingness to help". A second student healthcare setting study found that perceived promptness was positively related to student satisfaction (Senic & Marinkovic, 2013). A recent qualitative study (Randall & Bewick, 2016) looked at counselor perceptions in the United Kingdom for improving service quality to students.…”
Section: Measuring Ucc Pspmentioning
confidence: 99%